'How Does the Movement Work? Above All, Inefficiently'. Political Outcomes of the Polish LGBT* Movement. (2nd January 2021) - Bielska, Beata
ABSTRACT: The aim of this article is to analyse the political outcomes of the LGBT* movement in Poland, referring to civil unions, marriage equality, adoption, homophobic and transphobic hate crimes and Gender Recognition Act. I argue that the movement has become a recognizable political actor but has not achieved any legislative goal. It is based on an extensive qualitative research project conducted between 2013 and 2016, but includes also the newest information about the context and the movement. Methodologically it is situated in the critical orientation in sociology and theoretically in the field of social movement studies. Respondent's comments on the conclusions are also presented.